NEUROSCIENCES VS. CRIMINAL LAW - Castro, Sabrina E. (2021)
The debates on the relationship between Neurosciences and Criminal Law may seem very current and novel, however, it could well be argued that the origins are long-standing. There has always been the debate between “determinism vs. indeterminism ”, that idea that the world is predetermined - that everything has a cause and can be explained according to natural laws or not. This traditional debate could be carried over to today. However, it will no longer be such a philosophical or cosmological debate, but it will be a more objective debate listed behind empirical methods, based on experience and on the concrete observation of certain facts. Specifically, it will be a debate that will have to do with the specific data that the neurosciences provide us, and to what extent this influences - or could influence - current Criminal Law, at the same time that it will rethink in what way the incorporation of the Data provided by other sciences and disciplines condition - or could condition - to maintain the Criminal Law that we have today.- In this way, what affects the debate is the maintenance or not, of a Criminal Law of Guilt by In fact, that is to say that the debate will focus on the material basis of guilt, on the idea that human beings are guilty only insofar as they act freely.